Modification of Starch with Allopurinol and Ampicilline as Sulfonamide Derivatives - A, Firyal M; Rahi, Firas A; KH, Wessal M; Alshather, Ahmed I; K, Shurooq S (Al-Nahrain Journal of Science, 2018)
The available hydroxyl groups on the starch chains potentially exhibit reactivity specific for alcohols which were modified with chlorosulfonic acid at zeroºC to yield starch sulfonic acid P1, then substitution of P1 to its corresponding drug derivatives such as with allopurinole or ampicilline P2 and P3 respectively. The new prepared starch derivatives were characterized byFT.IR and UV. Spectroscopy. The physical properties were studied. Thermal analyses were recorded and swelling % were studied, Controlled drug release were measured at different pH values at 37ºC. Intrinsic viscosities were measured using Ostwald viscometer at 30ºC. This technique through which stomach drug targeting can be achieved as timed released system.